THE MINERALOGY STUDY OF BAUXITE DEPOSIT PT ANTAM TBK UNIT GEOMIN IN KENCO AREA LANDAK DISTRICT OF WEST KALIMANTAN - Jafar, Nurliah
Indonesia is a country with a tropical climate that allows for a high degree of weathering. Bauxite is the rocks weathering product that has a high content of aluminum, a low content of iron and a slightly lower content of quartz. Bauxite deposit formation is controlled by parent rock which is rich with Al element, tropical climate condition and geomorphological condition that allow the formation of product accumulation of parent rock weathering. Modified silicate minerals due to weathering elements cause the release of silica element from the crystalline bond and the release of some part of iron element that makes the aluminum element be concentrated as residue deposit. Mineralogical studies in the research area is fulfilled by petrographic analysis at 15 samples of parent rock to determine the constituent of minerals and the parent rock types; X_ray Diffraction (XRD) analysis in 16 samples of bauxite which estimated to represent of overburden horizon, ore bauxite horizon, clay horizon and parent rock horizon to determine the type and composition of minerals constituent of bauxite; X_Ray Fluorescence (XRF) analysis in 297 samples of washed bauxite and 15 parent rock to samples to determine the content of Al?O?, Fe?O?, TiO?, and SiO?. Based on petrographic analysis, the bauxite parent rocks in the research erea are granodiorite, granodiorite porphyry, gabbro porphyry and basalt porphyry. The main minerals of those types of rock are orthoclase, plagioclase, pyroxene and biotite. The igneous rocks are intermediate. The bauxite type is gibbsite bauxite based on X_ray diffraction ( XRD ) analysis with a dominant frequency of gibbsite appearance compared to corondum mineral as an alumina group. The bauxite is classified as ortobauksit based on X_ray diffraction (XRD) analysis with mineral appearance in each horizon. The mineral groups at the overburden horizon, ore bauxite horizon and clay horizon are alumina, iron, titanium, silicate, carbonate, sulfide and sulfate, while the parent rock groups are iron, titanium, silicate, sulfide and sulfate. Bauxite generally is deposited in relatively steep slope.